2020
DOI: 10.7150/jca.31422
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone Inhibites Bladder Cancer Cell Proliferation and Promotes Apoptosis via the PTEN/PI3K/AKT Pathway

Abstract: Cryptotanshinone (CTT), extracted from the root of Salvia miltiorrhiza Bunge (Danshen), exhibits activities against a variety of human cancers in vitro and in vivo. The purpose of this study was to investigate the potential inhibitory effect of CTT on bladder cancer. In this study, we found that CTT inhibited bladder cancer cell proliferation, migration, and invasion and promoted apoptosis. In addition, CTT modulated the expression of proteins via the PI3K/AKT pathway, and the inhibition of PI3K/AKT signalling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 40 publications
1
26
1
Order By: Relevance
“…Besides, PI3K/Akt axis triggers resistance of cancer cells into chemotherapy, PTEN is able to inhibit PI3K/Akt signaling pathway (Alzahrani, 2019). Notably, accumulating data demonstrates that CT can target PI3K/Akt signaling pathway, its down‐stream (such as GSK‐3β) and upstream (PTEN) mediators (Kim, Kang, & Kwon, 2018; Liu et al, 2020). Inhibition of PI3K/Akt pathway by CT mediates its inhibitory effect on migration and proliferation of cancer cells (Zhang, Wen, et al, 2018).…”
Section: Cryptotanshinone As a Modulator Of Molecular Pathways In Difmentioning
confidence: 99%
“…Besides, PI3K/Akt axis triggers resistance of cancer cells into chemotherapy, PTEN is able to inhibit PI3K/Akt signaling pathway (Alzahrani, 2019). Notably, accumulating data demonstrates that CT can target PI3K/Akt signaling pathway, its down‐stream (such as GSK‐3β) and upstream (PTEN) mediators (Kim, Kang, & Kwon, 2018; Liu et al, 2020). Inhibition of PI3K/Akt pathway by CT mediates its inhibitory effect on migration and proliferation of cancer cells (Zhang, Wen, et al, 2018).…”
Section: Cryptotanshinone As a Modulator Of Molecular Pathways In Difmentioning
confidence: 99%
“…Therefore, the exploration of new drugs and new methods for the treatment of lung cancer requires an urgent attention. A large number of basic research and clinical practice have shown that natural products can play an important role in the tumour prevention and rehabilitation of cancer patients ( Kim et al, 2020 ; Liu et al, 2020 ; Yeh et al, 2020 ). Their reliable source and high safety are the features, which make them the main source of new drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Activated caspase-9 can activate procaspase-3 downstream, which can further cleave PARP, leading to the apoptotic cascade 13,42,47 . Activated caspase-3 also induces the downstream mitochondrial apoptotic pathway, thereby inhibiting AKT 43,[48][49][50][51] . Time-dependent cleavage of caspase-3, caspase-9, and PARP was observed in the DHW-208 treatment cells indicating that DHW-208 can reduce activity of the caspase (intrinsic) pathway.…”
Section: Discussionmentioning
confidence: 99%